CD-Markers as an immunological aspect in patients with visceral leishmaniasis - Zangor Al-Autabbi, Jabbar R.; Hamed. Al-Rubayee, Zainab A. (Journal of the Faculty of Medicine Baghdad, 2010)
Back ground: Visceral leishmaniasis is an endemic protozoan disease in Iraq. Recovery from this disease confers a solid and permanent immunity. Immunological assessment of our patients was carried out and the results showed a significant reduction in the percentage of CD3, CD56 and a significant increase in the percentage of CD19 in the peripheral blood lymphocyte of VL in comparison with control group.Patients and methods: Indirect immunofluorescence technique analysis was performed to detect the percentage of CD3, CD19and CD56 positive lymphocytes.Results: Our results in the patients groups showed decrease in the percentage of CD3, CD56 and increase in the percentage of CD19. Follow up of patients after treatment showed a significant increase in the percentage of CD3, CD56, but they were still lower than their normal range .Conclusion:- CD3,CD56, were decreased in VL infection then increased after treatment but it was less than its normal range, while CD19 was increased in VL when compared with control group.